Uncharted territory : investigating individual business ethics in Cyprus - Zopiatis, Anastasios; Krambia-Kapardis, Maria (My University, 2008)
The research purpose of the study is to investigate and identify correlates of ethical behaviour and attitudes of individuals currently working or pursuing a business-related graduate degree in Cyprus. Analysis of the quantitative questionnaire revealed that the majority of the respondents had a concept of ‘ethical behaviour’, consider ethics important, and hold attitudes that are conducive to ethical behaviour in business. In addition, findings revealed significant differences in three correlates: age, gender and position. Finally, reflecting the findings, the authors suggest specific actions that aim to improve ethical decision making in the Cyprus business environment.
Keywords: Business ethics